Neurotrophic Factor Mediated Neurorestorative Effect of Pongamia pinnata Against Transient Cerebral Hypoperfusion and Reperfusion in Rats: Preliminary Histological and Molecular Level Evidence - Suganitha, Balasundaram; Jagadeesan, Vijayakumar; Sivanesan, Senthilkumar; Prathap, Lavanya; Mundugaru, Ravi; Alzerwi, Nasser; Saraswathi, Ilango; Saikarthik, Jayakumar (International journal of morphology, 2024)
Stroke is the leading cause of acquired physical disability in adults and second leading cause of mortality throughout the world. Treatment strategies to curb the effects of stroke would be of great benefit. Pongamia pinnata is a recent attraction in medicine, owing to its abundant medicinal benefits with minimal side effects. The present study aimed to examine acute and subacute effect of Pongamia pinnata leaf extract on transient cerebral hypoperfusion and reperfusion (tCHR) in Wistar rats. 24 adult Wistar rats (12 each for acute and subacute study) were divided in to four groups each viz normal control group, tCHR + NS group, tCHR + 200mg/kg bw and tCHR + 400mg/kg bw groups. Cerebral ischemia induction was carried out by bilateral common carotid artery occlusion and reperfusion. Ethanolic extract of Pongamia pinnata leaves were orally administered for 7 days and 21 days after the surgical procedure for acute and subacute study respectively. Behavioural analysis, histological assessment, and estimation of mRNA levels of HIF-1, GDNF, BDNF and NF-kB were performed. In both acute and subacute study, there was significant improvement in the beam walking assay, neuronal count, decreased neuronal damage in histological sections and higher mRNA expression of BDNF and GDNF in the treatment groups. There was no significant difference in the expression of HIF1 and NF-kB. Thus, Pongamia pinnata has excellent neurorestorative property reversing many of the effects of ischemic stroke induced by tCHR in rats with the underlying mechanism being an improvement in the expression of neurotrophic factors GDNF and BDNF.